Negative poisson’s ratio of sulfides dominated by strong intralayer electron repulsion - Zhu, Yucheng (2024)
Geometrical variations in a particular structure or other mechanical factors are often cited as the cause of a negative Poisson's ratio (NPR). These factors are independent of the electronic properties of the materials. This work investigates a class of two-dimensional (2D) sulfides with the chemical formula MX2 (M = Ti, Cr, Mn, Fe, Co, X = S) using first-principles calculations. Among them, monolayered TiS2, CrS2, and MnS2 were found to exhibit a structure-independent NPR. The strong strain response of intra-layer interactions is responsible for this unique phenomenon. This can be traced to the lone pair of electrons of the S atoms and the weak electronegativity of the central atoms in multi-orbital hybridization. Our study provides valuable insights and useful guidelines for designing innovative NPR materials.